Discrimination of processing grades of olive oil and other vegetable oils by monochloropropanediol esters and glycidyl esters. (15th May 2018) - Yan, Jing; Oey, Sergio B.; van Leeuwen, Stefan P.J.; van Ruth, Saskia M.
Highlights: The MCPD esters and GEs in different grades of vegetable oils were investigated. 3-MCPD is a promising compound to classify different processing grades of oils. The capability of MCPD esters and GEs to identify olive oil adulteration is discussed. Refined/Pomace olive oils show higher MCPD esters and GEs contents. Daily intake limitation of different grades olive oils were announced. Abstract: In this study, the processing derived contaminants 2- and 3-monochloropropanediol (2- and 3-MCPD) esters and glycidyl esters (GEs) were analysed in 84 oil samples by GC–MS/MS for the discrimination of processing grades of olive oils as a potential authentication tool. Concentrations of 2- and 3-MCPD esters and GEs varied in the ranges 0–6 mg/kg, 0–1.5 mg/kg, and 0–1 mg/kg oil, respectively. The concentrations of the three compounds in lower grade olive oils were significantly higher (P < .001) than that in EVOO. A similar difference was observed for other refined and cold-pressed vegetable oils. The limit of fraud detection of lower grade oils in EVOO was 2% when using 3-MCPD esters, 5% for 2-MCPD esters, and 13–14% for GEs based on calculations of virtual mixtures of the current sample set. Especially the MCPD esters appear very specific and promising for the detection of lower processing grade oils in EVOO.